Dysregulated but not decreased salience network activity in schizophrenia - White, Thomas; Gilleen, James K.; Shergill, Sukhi S. (Frontiers in Human Neuroscience, 2013)
Effective estimation of the salience of environmental stimuli underlies adaptive behaviour, while related aberrance is believed to undermine rational thought processes in schizophrenia. A network including bilateral frontoinsular cortex (FIC) and dorsal anterior cingulate cortex (dACC) has been observed to respond to salient stimuli using functional magnetic resonance imaging (fMRI). To test the hypothesis that activity in this salience network (SN) is less discriminately modulated by contextually-relevant stimuli in schizophrenia than in healthy individuals, fMRI data were collected in 20 individuals with schizophrenia and 13 matched controls during performance of a modified monetary incentive delay task. After quantitatively identifying spatial components representative of the FIC and dACC features of the SN, two principal analyses were conducted. In the first, modulation of SN activity by salience was assessed by measuring response to trial outcome. First-level general linear models were applied to individual-specific time-courses of SN activity identified using spatial independent component analysis. This analysis revealed a significant salience-by-performance-by-group interaction on the best-fit FIC component’s activity at reward outcome, whereby healthy individuals but not individuals with schizophrenia exhibited significantly greater distinction between the response to hits and misses in high salience trials than in low salience trials. The second analysis aimed to ascertain whether SN component amplitude differed between the study groups over the duration of the experiment. Independent-samples T-tests on back-projected, percent-signal-change scaled SN component images importantly showed that the groups did not differ in the overall amplitude of SN expression over the entire dataset. These findings of dysregulated but not decreased SN activity in schizophrenia provide physiological support for mechanistic conceptual frameworks of delusional thought formation.